Produção heteróloga dos peptídeos antimicrobianos Cm-p5 e Cn-AMP1 em sistema procarioto - Cobacho, Nicole Berwanger (2017)
The resistance of microorganisms to commonly used antibiotics has increased dramatically in recent years, suggesting that we will soon enter a post-antibiotic era where no therapy currently used will be effective in the fighting against infection. Thus, the search and study of new drugs and models of action of compounds that prevent or reduce the development of pathogens is essential. In this context, antimicrobial peptides (PAMs) appear as a new generation of compounds that demonstrate a great therapeutic potential. These molecules present themselves in low concentration in the organism of origin, making their isolation from natural sources an expensive and often impracticable process. In order to obtain a greater quantity of these peptides, recombinant expression via the heterologous system can be considered an efficient alternative in terms of time, cost and productivity. In 2009, Mandal et al. isolated three coconut water (Coco nucifera) peptides, called Cn-AMP1-2 and -3. Among them, Cn-AMP1 presented better activity against bacteria and fungi of medical importance. Subsequently, Lopez-Abarrategui et al. in 2012 isolated peptides with antimicrobial activity from the mollusk Cenchritis muricatus called Cm-p1 and Cm-p2. From these, a series of variant peptides were theoretically proposed in silico and evaluated against Candida albicans and the peptide named Cm-p5 demonstrated, among them, better antifungal activity. In this work, several constructs containing the peptides Cm-p5 and Cn-AMP1 were drawn in tandem and inserted into the pETSUMO (Life Technologies) vector. Genes were expressed in large quantities in strains derived from Escherichia coli BL21 (DE3) and after affinity column purification, they were evaluated, still fused with SUMO protein, against pathogenic microorganisms. However, none of the expressed peptides demonstrated bactericidal activity against the strains evaluated.